Diverse heterocyclic scaffolds as dCTP pyrophosphatase 1 inhibitors. Part 2: Pyridone- and pyrimidinone-derived systems. Issue 15 (1st August 2017) - Llona-Minguez, Sabin; Häggblad, Maria; Martens, Ulf; Johansson, Lars; Sigmundsson, Kristmundur; Lundbäck, Thomas; Loseva, Olga; Jemth, Ann-Sofie; Lundgren, Bo; Jensen, Annika Jenmalm; Scobie, Martin; Helleday, Thomas
Graphical abstract: Abstract: Two screening campaigns using commercial (Chembridge DiverSET) and proprietary (Chemical Biology Consortium Sweden, CBCS) compound libraries, revealed a number of pyridone- and pyrimidinone-derived systems as inhibitors of the human dCTP pyrophosphatase 1 (dCTPase). In this letter, we present their preliminary structure-activity-relationships (SAR) and ligand efficiency scores (LE and LLE).